Acute alveolitis following infliximab therapy for psoriasis. (11th July 2012) - Bale, Jessica; Chee, Paul
Abstract Infliximab is a high‐affinity recombinant chimeric immunoglobulin‐1 monoclonal antibody directed against tumour necrosis factor‐alpha. It is used to treat a range of inflammatory disorders including psoriatic joint and skin changes. Acute interstitial lung disease is a rare but potentially fatal complication of therapy. We report the case of a 67‐year‐old man with severe psoriasis who presented with acute alveolitis shortly after his third infusion of infliximab. The infliximab was discontinued and investigations did not reveal an infective cause. His respiratory signs and symptoms improved quickly with corticosteroid therapy. Clinicians should be aware of this uncommon but potentially serious complication.